A review of magnetic resonance enterography based Crohn’s disease activity indices in paediatric patients - B. Herman, Roma; Dumnicka, Paulina; Fyderek, Krzysztof (Gastroenterology Review/Przegląd Gastroenterologiczny, 2022)
Magnetic resonance enterography (MRE) is a commonly used method for non-invasive diagnosing and following of inflammatory bowel disease (IBD). Numerous reviews that compare and discuss MRE-based Crohn’s disease (CD) activity indices for adults have been published; however, no reviews of this kind have been published for children. Following a PubMed database literature search (January 2008 – November 2021), out of 316 research papers, 10 original papers about MRE-CD activity indices were included in the analysis. Four MRE-based scoring systems were discussed: Magnetic Resonance Index of Activity (MARIA), the Crohn’s Disease Magnetic Resonance Imaging Index (CDMI), the Magnetic Resonance Enterography Global Score (MEGS) and the Visual Analogue Scale (VAS). This review revealed that in the last 13 years, studies have proven that MRE-based CD activity indices correspond with endoscopic findings and clinical scores of CD activity.